Вы находитесь на странице: 1из 24
University of Zimbabwe MT 115 CALCULUS FOR ENGINEERING Chapter 2 Author: T.V. Mupedza Department: Mathematics

University of Zimbabwe

MT 115 CALCULUS FOR ENGINEERING

Chapter 2

Author:

T.V. Mupedza

Department:

Mathematics

of Zimbabwe MT 115 CALCULUS FOR ENGINEERING Chapter 2 Author: T.V. Mupedza Department: Mathematics August 28,

August 28, 2019

Sequences

Definition 0.0.1. A sequence is a set of numbers u 1 , u 2 , u 3 , and formed according to a definite rule.

in a definite order of arrangement

Each number in the sequence is called a term and u n is called the nth term.

{u n }, e.g., {u n } = 2n, where u 1 = 2, u 2 = 4, u 3 = 6 and so

on. The sequence is called finite or infinite according as there are or are not a finite number of terms.

The sequence

u 1 , u 2 , u 3 ,

is written briefly as

Recursion Formula or Recurrence Relations So far we have seen that a sequence {U n } may be defined by giving a formula for {U n } in terms of n. For example

U n = 2n 2 5n + 4

.

n 2 + 1 We can also define sequences by giving a relation or formula that connect successive terms of a sequence and specifying the value or values of the first term or the first and second terms etc. The formula or relation linking the terms is called a recursion formula or recurrence relation.

Example:

Find the values of the first four terms of the sequence defined by

u n+1 =

2

,

u n

u 0 = 1,

n N.

Solution:

You Try It: Define recursively

u

1

=

u 0+1 = 2

u

0

u 2 = u 1+1 = 2

u

1

u 3 = u 2+1 = 2

u

2

=

=

1 2 = 2

2 2 = 1

2 = 2.

= 1

a 0 = a 1 = 1,

and

a n = a n1 + 2a n2 , n 2.

Find a 6 recursively.

1

0.1

Limits of Sequences

1

Lets consider the sequence u n =

n . terms of the sequence tend to or approach 0.

Definition 0.1.1. A number L is called the limit of an infinite sequence a 1 , a 2 , a 3 ,

for any positive number ε, we can find a positive number N depending on ε such that |a n L| < ε

for all integers n > N . We write lim

We see that the

The sequence has the terms 1,

1

2 ,

1

3 ,

1

4 ,

.

.

.

.

or {a n }, if

n a n = L.

If {a n } is a convergent sequence, it means that the terms a n can be made arbitrarily close to L for n sufficiently large.

be made arbitrarily close to L for n sufficiently large. Example: If u n = 3

Example: If u n = 3 + 1

= 3n + 1

n n

lim

n u n = 3.

, the sequence is 4,

7 , 10

2

3 ,

and we can show that

If the limit of a sequence exists, the sequence is called convergent, otherwise, it is called divergent.

Example: Prove that lim

n→∞

1

n = 0.

Let ε > 0, we can find N (ε) such that n 0

1

1

n

=

1

< ε.

n

1

n = 0.

Proof:

=

Taking N to be the smallest integer greater than 1 ε , we have, lim

n→∞

2

But n >

1

ε .

So N

=

1

ε .

You Try It: Prove that lim

n0

1

p = 0 if p N.

n

Example: Use the definition of a limit to prove that lim

n→∞

2n 1

3n + 2 =

2 .

3

Proof: Let ε > 0, we can find N (ε) such that

2n 1 3n + 2 3 2

=

3(2n 1) 2(3n + 3)

3(3n + 2)

=

6n 3 6n 4

3(3n + 2)

=

7

3(3n + 2)

=

7

3(3n + 2)

7

3(3n + 2)

n

<

ε

7 6ε

>

9ε

.

Take N = 7 6ε . So taking N to be the smallest integer greater than 7 6ε , we have

2n 1 3n + 2 2 3

9ε < ε , i.e.,

lim

n→∞

2n 1

3n + 2 = 3

2 .

9ε

0.2 Theorems on Limits

If lim

n a n = A and lim

n b n = B, then

1. n (a n + b n ) = lim

lim

n a n +

n b n = A + B.

lim

2. n (a n b n ) = lim

lim

n a n lim

n b n = A B.

3. n (a n · b n ) = ( lim

lim

n a n )( lim

n b n ) = AB.

4. lim

n→∞

lim

a n→∞ a n

n

=

b n→∞ b n

n

lim

=

A

B

if

n b n = B

lim

= 0.

< ε

5. The limit of a convergent sequence {u n } of real numbers is unique.

Proof: We must show that if lim

n u n = l 1 and

n u n = l 2 , then l 1 = l 2 . By hypothesis, given any

lim

ε > 0, we can find N such that |u n l 1 | < 2 ε

when n > N and |u n l 2 | < 2 ε

when n > N . Then

|l 1 l 2 | = |l 1 u n + u n l 2 | ≤ |l 1 u n | + |u n l 2 | < ε

2 + 2 ε = ε,

i.e., |l 1 l 2 | is less than any positive ε (however small) and so must be zero, i.e., l 1 l 2 = 0 =l 1 = l 2 .

3

Example: If lim

n a n = A and lim

n b n = B, prove that lim

n (a n + b n ) = A + B.

Proof: We must show that for any ε > 0, we can find N > 0, such that |(a n + b n ) (A + B)| < ε

for all n > N .

We have

|(a n + b n ) (A + B)| = |(a n A) + (b n B)| ≤ |a n A| + |b n B|.

By hypothesis, given ε > 0 we can find N 1 and N 2 such that |a n A| <

|b n B| < 2 ε for all n > N 2 . Then

|(a n + b n ) (A + B)| < ε

2 + 2 ε = ε

for all n > N where N = max(N 1 , N 2 ). Hence lim

n (a n + b n ) = A + B.

ε

2

for all n > N 1

and

0.3 Sequences Tending to Infinity

n tends to infinity, n → ∞ (n grows or increases beyond any limit ). Infinity is not a number and the sequences that tend to infinity are not convergent.

We write lim

n a n = , if for each positive number M , we can find a positive number N (depending

on M ) such that a n > M for all n > N .

Similarly, we write lim

n a n = −∞, if for each positive number M , we can find a positive number N

such that a n < M for all n > N .

Example: Prove that (a)

n 3 2n1 =

lim

(b)

n (1 2n) = −∞.

lim

Proof: (a) If for each positive number M we can find a positive number N such that a n > M for

Taking N to be

all n > N , then 3 2n1 > M

2 ln M

1

ln 3

+ 1 .

when (2n 1) ln 3 > ln M , i.e., n >

the smallest greater than

1 ln M

2

ln 3

+ 1 , then

n→∞ 3 2n1 = .

lim

(b) If for each positive number M , we can find a positive number N such that a n < M for all

> N , i.e., 1 2n < M when 2n 1 > M or n > 1 2 (M + 1). Taking N to be the smallest integer

greater than

n

2 (M + 1), we have lim

1

n (1 2n) = −∞.

4

0.4

Bounded and Monotonic Sequences

A sequence that tends to a limit l is said to be convergent and the sequence converges to l.

sequence may tend to +or −∞, and is said to be divergent and it diverges to +or −∞.

A

, where M is a constant, we say that the sequence {u n } is bounded

above and M is called an upper bound. The smallest upper bound is called the least upper bound (l.u.b).

If u n M for n = 1, 2, 3,

If

u n m, the sequence is bounded below and m is called a lower bound. The largest lower bound

is

called the greatest lower bound (g.l.b).

If m u n M , the sequence is called bounded, indicated by |u n | ≤ P . (Every convergent sequence is bounded, but the converse is not necessarily true)

If u n+1 u n , the sequence is called monotonic increasing and if u n+1 > u n it is called strictly

increasing.

If u n+1 u n , the sequence is called monotonic decreasing, while if u n+1 < u n it is

strictly decreasing.

Examples: 1. The sequence 1, 1.1, 1.11, 1.111,

2. The sequence 1, 1, 1, 1, 1,

is bounded and monotonic increasing.

is bounded but not monotonic increasing or decreasing.

Definition 0.4.1. A null sequence is a sequence that converges to 0, e.g., u n =

1

n 10 , n 11.

If {u n } does not tend to a limit or +or −∞, we say that {u n } oscillates (or is an oscillating

sequence). It can oscillate finitely (bounded) or infinitely (unbounded).

Examples: u n = (1) n ,

u n = (1) n n.

0.5 Limits of Combination of Sequences

n→∞ 2 n + n 3

1

2 or

We want to be able to evaluate limits, for example, of the form lim

n→∞ 2 n + n 3

1

2 =

Example: lim

1

n 2 lim n + 3 lim

lim

n→∞

n→∞

1

n 2 = 2 0 + 0 = 2.

Example: lim

n→∞

3n 2 5n

5n 2 + 2n 6 =

lim

n→∞

3 − 5 n 2 5 + n − n 6 2
3 − 5
n
2
5 +
n − n 6 2

=

3 + 0

5 + 0 + 0 =

3 .

5

5

lim

n→∞

5 2n 2 4 + 3n + 2n 2 .

n ( n + 1 n) ·

n + 1 + n =

n + 1 + n

· √ √ n + 1 + √ n = n + 1 + √ n

Example: lim

n ( n + 1 n) = lim

lim

n→∞

1

( √ n + 1 − √ n ) = lim l i m n →∞

n + 1 + n

= 0.

0.6 Squeeze Theorem

If

n a n = l =

lim

n c n = l.

lim

n b n and there exists an N

lim

such that a n

c n

b n ,

Example: Find lim

n→∞

cos n

n

.

Solution: We know that 1 cos n 1

1

=⇒ −

=lim

n 1 cos n cos n n

1

n

n =⇒ − lim

n→∞

lim

n→∞

= 0.

n→∞

n

cos n

n

lim

n→∞

1

n =0

lim

n→∞

cos n

n

for all

0

n

>

N , then

6

Infinite Series

One important application of infinite sequences is in representing infinite summations. If {a n } is an infinite sequence, then

n=1

a n = a 1 + a 2 + a 3 + ···

is called an infinite series (or simply a series). The numbers a 1 , a 2 , a 3 ,

the series. To find the sum of an infinite series, consider the following sequence of partial sums.

are called the terms of

S

S

S 3

.

.

.

S n

2

1

=

=

=

=

=

a a 1 + a 2 a 1 + a 2 + a 3

.

a 1 + a 2 + a 3 + ··· + a n .

1

.

.

If this sequence of partial sums converges, then the series is said to converge and has the sum indicated in the following definition.

0.7 Definition of Convergent and Divergent Series

For the infinite series a n , the nth partial sum is given by

S n = a 1 + a 2 + a 3 + ··· + a n .

If the sequence of partial sums {S n } converges to S, then the series a n converges. The limit S is called the sum of the series. If {S n } diverges, then the series diverges.

7

Example 0.7.1. The series

n=1

1

2 n =

1

2 + 4 + 8 +

1

1

1

16 + · · · has the following partial sums.

Because lim

n→∞

2 n 1

2

n

S 1 =

S 2 =

s 3 =

=

s n =

.

.

.

1

2

1

1

3

2

1

+ 4 = 4

7

+ 4 + 8 = 8

1

.

1

1

.

2

.

1

2 + 4 +

.

1

8 + ··· +

1

2

n

= 2 n 1

2

n

.

= 1, it follows that the series converges and its sum is 1.

Example 0.7.2. The nth partial sum of the series

n=1

n n + 1 = 1

1

1

2 +

1

1

2 1

3 + 3

1

1

4 + ···

1

is given by S n = 1 n + 1 . Because the limit of S n is 1, the series converges and its sum is 1.

Example 0.7.3. The series

partial sums diverges.

n=1

1 = 1 + 1 + 1 + · · ·

diverges, because S n = n and the sequence of

The series in Example (0.7.2) is a telescoping series. That is, it is of the form

(b 1 b 2 ) + (b 2 b 3 ) + (b 3 b 4 ) + (b 4 b 5 ) + ···

note that b 2 is canceled by the second term, b 3 is canceled by the third term and so on. Because the nth partial sum of the series is S n = b 1 b n+1 , it follows that a telescoping series will only converge if and only if b n approaches a finite number as n → ∞. Moreover, if the series converges, then its sum is

S = b 1

Example 0.7.4. Find the sum of the series

n=1

n→∞ b n+1 .

lim

2

4n 2 1 .

Solution: Using partial fractions, we can write

a n =

2

4n 2 1 =

2

(2n 1)(2n + 1) =

1

2n 1

1

2n + 1 .

From the telescoping form, we can see that the nth partial sum is

S n =

1

1

1

3 +

1

3 1 5 + ··· +

8

1

2n 1

1 + 1 = 1

2n

1

2n + 1 .

Thus, the series converges and its sum is 1. That is,

n=1

2

4n 2

1 =

n→∞ 1

n S n = lim

lim

1 + 1 = 1.

2n

0.8 Geometric Series

A geometric series with ratio r is given by

n=0

ar n = a + ar + ar 2 + · · · + ar n + ··· , a

= 0.

Theorem 0.8.1. A geometric series with ratio r diverges if |r| ≥ 1. If 0 < |r| < 1, then the series

converges to the sum

ar n =

a

1 r ,

0 < |r| < 1.

n=0

Example 0.8.1. The geometric series

3

2 n =

n=0 n=0 has a ratio of r = with a = 3. 1 2 a
n=0
n=0
has
a ratio
of
r
=
with a
=
3.
1 2
a 3
S =
= 6.
1 − r =
1 − 1
2

3 2 n = 3(1) + 3 1 2 + 3

1

1

2 2

+ ···

Because 0 <

|r|

<

1, the series converges and its sum is

0.8.1 Properties of Infinite Series

If a n = A and b n = B and c is a real number, then the following series converge to the

indicated sums. (i) ca n = cA

(ii)

(a n ± b n ) = a n ± b n = A ± B.

n-th Term Test for Divergence

Limit of nth Term of a Convergent Series

If

the series a n converges, then the sequence {a n } converges to 0.

If

the sequence {a n } does not converge to 0, then the series a n diverges.

9

0.9

Test for Convergence or Divergence of Series

In this and the following section, we will study several convergence tests that apply to series with positive terms.

0.9.1 The Integral Test

If f is positive, continuous, and decreasing for x 1 and a n = f (n), then

either both converge or both diverge.

Example 0.9.1. Apply the integral test to the series

n=1

n

n 2 + 1 .

n=1

a n and f (x) dx

1

Because f (x) =

obtain

x + 1 satisfies the conditions for the integral test (check this), we can integrate to

x 2

1

x

2

x + 1 dx

=

1

2 x 2

2x + 1 dx = 1

2

1

b→∞ b

lim

1

1 b ln(x 2 + 1) b

2

1

1 b [ln(b 2 + 1) ln 2]

2

=

lim

lim

=

= .

2x

x 2 + 1 dx

Thus, the series diverges.

Example 0.9.2. Apply the integral test to the series

n=1

1

n 2 + 1 .

Solution: Because f (x) =

obtain

1 + 1 satisfies the conditions for the integral test, we can integrate to

x 2

1

dx

x

2

+ 1

=

=

=

b→∞ b

lim

1

dx

x

2

+ 1 =

b lim tan 1 x b

1

b (tan 1 b tan 1 1)

lim

π

2

π

4

= π

4 .

Thus, the series converges.

10

0.9.2

pSeries and Harmonic Series

A

is

series of the form

n=1

1

n p =

1

1

1 p + 2 p +

1

3 p + ···

a pseries, where p is a positive constant. For p = 1, the series

is

Theorem 0.9.1. The pseries

the harmonic series.

1

n

n=1

 

1

1

= 1 +

2

+

3

1

1

1 p + 2 p +

+ ···

1

3 p + ···

1

n p =

n=1

(i) converges if p > 1 and (ii)

diverges if 0 < p 1.

Example 0.9.3. From the Theorem it follows that the harmonic series

diverges.

n=1

1

1

1

n

= 1 +

2

+

3

+ ···

0.10 Comparisons of Series

0.10.1 Direct Comparison Test

This is a test for positive-term series. It allows you to compare a series having complicated terms with a simpler series whose convergence or divergence is known.

Direct Comparison Test

Theorem 0.10.1. Let 0 a n b n for all n.

1.

If

n=1

b n converges, then

n=1

a n converges.

11

2.

If

n=1

a n diverges, then

n=1

b n diverges.

Example 0.10.1. Determine the convergence or divergence of

n=1

1

2 + 3 n .

Solution: This series resembles

yields

n=1

1

n (Convergent geometric series). Term-by-term comparison

3

a n =

1 1

2 + 3 n <

n = b n ,

3

n 1.

Thus, by the Direct Comparison Test, the series converges.

Example 0.10.2. Determine the convergence or divergence of

n=1

1

2 + n .

Solution: The series resembles

n=1

1

2 (Divergent pseries). Term-by-term comparison yields

1

n

1

2 + n

1

n ,

n 1

which does not meet the requirements for divergence. Still expecting the series to diverge, we can

compare the given series with

parison yields

n (Divergent Harmonic series). In this case, term-by-term com-

n=1

1

a n =

1 1

n

2 + n = b n ,

n 4

and, by the Direct Comparison Test, the given series diverges.

0.10.2 Limit Comparison Test or Quotient Test

Often a given series closely resembles a pseries or a geometric series, yet we cannot establish the term-by-term comparison necessary to apply the Direct Comparison Test. We can apply a second comparison test, called the Limit Comparison Test.

Limit Comparison Test

Suppose that a n > 0 and b n > 0 and

n→∞ a n

n

lim

b

= L where L is finite and positive. Then the two

series a n and b n , either both converge or both diverge. If L = 0 and b n converges, then

a n converges. If L = and b n diverges, then a n diverges.

12

Example 0.10.3. Show that the following harmonic series diverges.

n=1

1

an + b ,

a > 0, b > 0.

n=1

1

n we have

1

an+b

1

n

1

a . Because this limit is

Solution: By comparison with

grater than 0, we can conclude from the Limit comparison Test that the given series diverges.

n

an + b =

lim

n→∞

= lim

n→∞

The limit Comparison Test works well for comparing a messy algebraic series with a pseries. In choosing an appropriate pseries, we must choose one with an nth term of the same magnitude as the nth term of the given series.

Given series

Comparison series

Conclusion

1

1

Both series converge.

3n 2 4n + 5

n 2

n=1

n=1

 

1

3n 2

1

   

n

Both series diverge.

n=1

n=1

n 2 10

4n 5 + n 3

1

n

3

 

n 2

n 5 =

Both series converge.

n=1

n=1

n=1

0.11 Alternating Series

So far, most series we have dealt with have had positive terms. In this section, we will study series that contain both positive and negative terms. The simplest such series is an alternating series, whose terms alternate in sign. For example, the geometric series

n=0

1 2 n

=

n=0

1

(1) n 2 n = 1

1

2 + 4

1

1 1

8 +

16 − ···

1

is an alternating geometric series with r = 2 . Alternating series occur in two ways, either the odd terms are negative or the even terms are negative.

Alternating Series Test

Let a n > 0. The alternating series

conditions are met.

n=1

(1) n a n and

13

n=1

(1) n+1 a n converge, if the following two

1.

a n+1 a n for all n.

2.

lim

n a n = 0.

Example 0.11.1. Determine the convergence or divergence of

n=1

(1) n+1 1

n .

1

n + 1

1

for all n and the limit (as n → ∞) of

1

is 0, we can apply the

n

n

Solution: Because

Alternating Series Test to conclude that the series converges. (This series is called the alternating

harmonic series)

Example 0.11.2. Determine the convergence or divergence of

n=1

n

(2) n1 .

Solution: To apply the Alternating Series Test, note that, for n 1,

Hence, a n+1 = n + 1

2 n

2

1

2

n1

2 n (n + 1)2 n1 n + 1

2

n

n

n

+ 1

n

n2 n

n

+ 1

n

2 n1 .

n

2 n1 = a n for all n. Furthermore, by L’Hopital’s rule,

lim

x→∞

x

2 x1 =

lim

x→∞

1

2 x1 (ln 2) = 0 =

lim

ninf

n

2 n1 = 0.

Therefore, by the Alternating Series Test, the given series converges.

Cases for which the Alternating Series Test Fails

Example 0.11.3. The alternating series

n=1

(1) n+1 (n + 1)

n

= 2

1

3 + 4

2

3 4 + 6 5 − ···

5

passes the first condition in the alternating series test because a n+1 a n for all n. We cannot apply the Alternating Series Test, because the series does not pass the second condition.

The alternating series

2

1

1

1

+ 2

2

1

2 + 3

2

1

3 + 2

1

1

4 + ···

passes the second condition because a n approaches 0 as n → ∞. We cannot apply the Alternating

Series Test, however, because the series does not pass the first condition.

14

0.12

Absolute and Conditional Convergence

Occasionally, a series may have both positive and negative terms and not be an alternating series, for example, the series

n=1

sin n

n 2

=

sin 1

1

+ sin 2 + sin 3

4

9

+ ···

has both positive and negative terms, yet it is not an alternating series. One way to obtain some information about the convergence of this series is to investigate the convergence of the series

n=1

sin n

n 2

. By direct comparison, we have | sin n| ≤ 1, for all n, so

sin n

n

2